Answer: Angle AFB is congruent to angle CEB because alternate interior angles are congruent.
Step-by-step explanation:
Given: ,
And, ac and ef are intersecting each other at point b.
Prove: Triangle abf is similar to triangle cbe
Since, (Reflexive)
,
⇒ ef is the common transversal of parallel lines fa and ec.
(Because Alternative interior angles are congruent)
Thus, By AA similarity postulate,
the question does not present the options, but thisdoes not interfere with the resolution
we know that
Perimeter of rectangle=2*[W+L]
where
L is the length of rectangle
W is the width of rectangle
Perimeter=18 cm
so
18=2*[W+L]-----> divide by 2------> 9=W+L
Let
x-------> L
y-------> W
then
x+y=9
using a graph tool
see the attached figure
the slope of the line is m=1
the x intercept is the point (9,0)
the y intercept is the point (0,9)
The relationship between the width and length of a rectangle given a constant perimeter is inverse; as the length increases, the width decreases proportionally. The graph representing this relationship would feature the length on the x-axis and width on the y-axis, and the line would represent all pairs of length and width that satisfy the equation
The problem in question asks to find the relationship between the width and length of a rectangle given its perimeter. In the given expression,
P = 2l + 2w
, where P is the perimeter, l is the length, and w is the width of the rectangle. Given that P = 18 cm, the relationship between the width and length can be represented by the equation
w = (P - 2l)/2
which implies that as the length increases the width decreases proportionally to maintain the constant perimeter. We must then create a graph where the x-axis represents the length and the y-axis represents the width, and a line representing possible solutions (l, w) that satisfy both the equation and the conditions given (length and width must be greater than 0).
#SPJ11
Answer:
a = - 2 , a = 6
Step-by-step explanation:
a² - 4a - 12 = 0
consider the factors of the constant term (- 12) which sum to give the coefficient of the a- term (- 4)
the factors are + 2 and - 6, since
+ 2 × - 6 = - 12 and + 2 - 6 = - 4
use these factors to split the a- term
a² + 2a - 6a - 12 = 0 ( factor the first/second and third/fourth terms )
a(a + 2) - 6(a + 2) = 0 ← factor out common factor (a + 2) from each term
(a + 2)(a - 6) = 0 ← in factored form
equate each factor to zero and solve for a
a + 2 = 0 ( subtract 2 from each side )
a = - 2
a - 6 = 0 ( add 6 to both sides )
a = 6
solutions are a = - 2 , a = 6
c. region
b. volume
d. area
Answer:
D area
Step-by-step explanation:
Answer:101
Step-by-step explanation:this is what ya gotta do:
add rsu and ust together
67+34=rst
rst =101